2009
DOI: 10.1186/1471-2458-9-236
|View full text |Cite
|
Sign up to set email alerts
|

Delay in the diagnosis of tuberculosis in Nepal

Abstract: BackgroundIdentifying reasons for delay in diagnosis and treatment of tuberculosis is important for the health system to find ways to treat patients as early as possible, and hence reduce the suffering of patients and transmission of the disease. The objectives of this study was to assess the duration of delay in the diagnosis of tuberculosis and to investigate its determinants.MethodsA cross-sectional survey was conducted using a structured questionnaire in 307 new tuberculosis patients registered by the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
56
5
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 1 publication
13
56
5
14
Order By: Relevance
“…No entanto, o retardo no diagnóstico aumenta a gravidade da doença e potencializa a disseminação da infecção na comunidade, elevando a mortalidade 29,30 .…”
Section: Discussionunclassified
“…No entanto, o retardo no diagnóstico aumenta a gravidade da doença e potencializa a disseminação da infecção na comunidade, elevando a mortalidade 29,30 .…”
Section: Discussionunclassified
“…20 A study in South India found longer diagnostic delay among men. 21 Another study in Nepal summarized that male patients experienced higher diagnostic delay 22 but several studies in developing countries reported longer diagnostic delay among women. 19,23 In our study, male patients experienced remarkable delay in diagnosis and constituted the higher percentage as compare to female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Median patient delay is as high as 8 weeks in Brazil [23] and 50 days in Nepal [18]; as medium as 23.5 days in Georgia [24], 3 weeks in Vietnam [25].…”
Section: Introductionmentioning
confidence: 99%
“…Delay was defined as any time period from the onset of symptoms to presentation, to diagnosis, to treatment initiation; or from presentation to diagnosis or treatment initiation; or else from diagnosis to treatment initiation based on their objective of study [14]. Almost all studies reviewed used "patient delay" contextually as the time interval between the onset of major symptoms of TB to the first presentation to formal health care facility [2] [5] [7] [8] [15]- [18]. One study defined "patient delay" as the time interval between the onsets of TB symptoms-and the first formal or informal health care received [19].…”
Section: Introductionmentioning
confidence: 99%